Assessment Practices and attitudes of pregnant women about anemia. - مصطفى, نسرين (Latakia University Journal -Medical Sciences Series, 2022)
The management of anemia in pregnant women and the prevention of its complications is of great importance in the nursing care provided to them. This requires that women adhere to health practices for prevention, treatment and prevention of anemia complications. These requirements are not complete until the pregnant woman has a positive and supportive approach to managing anemia. Therefore, the current descriptive study was conducted to identify the practices and attitudes of 200 pregnant women towards anemia in the women's clinic at Tishreen University Hospital. They were selected by appropriate random sampling method, and data were collected using a questionnaire developed by the researcher. The results showed that 62% of the women in the sample had an average level of anemia practices, Where the majority of them eat breakfast daily, They all do not eat ice, cornmeal, washing powder, baby powder, or clay. And that 51% of them have a positive attitude towards anemia, Whereas, the majority of them are not with drinking tea with their meal, not taking an iron tablet before eating, And feel that taking iron tablets has an important effect on the health of the fetus and the pregnant woman. The study recommended conducting educational sessions for pregnant women on the correct practices for managing anemia during pregnancy in terms of nutrition, health care request, and lifestyle. Encouraging them to continuously visit the health center for effective health supervision of them, enhancing their positive attitude towards anemia, and conducting a similar, broader and more comprehensive study at the country level with identifying the factors affecting the level of practices and attitudes of pregnant women towards anemia